(untitled) (Philological Studies, 2019)
The study of identity is a complex undertaking, which requires consideration of many aspects of collective and individual development. Given the complexity and comprehensiveness of the theme, our focus is on the Macedonian identity through the lens of historic research, specifically the beginnings of Macedonian historiography and both its non-formal and institutional development.